Beta-lactam comprehensive allergy management program in a community medical center - Lakhini Vyas; Karan Raja; Susan Morrison; Donald Beggs; Mark S. Attalla; Mitesh Patel; Mona Philips (Cambridge University Press, 2023)
Abstract Objective: The Beta-lactam Comprehensive Allergy Management Program (CAMP) was implemented to facilitate complete beta-lactam allergy history documentation in the electronic medical record (EMR) and increase beta-lactam utilization. The study objective was to assess the rate of complete allergy histories and days of antimicrobial therapy (DOT) before versus after CAMP implementation. Design: Quasi-experimental study with interrupted time-series analysis. Setting: Non-teaching, urban, and community medical center within a multi-hospital health system. Patients: Adult inpatients with a beta-lactam allergy receiving antimicrobial therapy. Methods: The multidisciplinary CAMP team screened, interviewed, and collected allergy history details of adult inpatients with a beta-lactam allergy receiving antimicrobial therapy starting January 4, 2021. Patients were stratified as high, moderate, or low risk of IgE-mediated allergy and referred to an allergist for skin testing or drug challenge. The EMR was updated with interview details and drug challenge or skin test results. The primary endpoint was rate of complete allergy history documentation before (12/1/18-4/1/19) compared to after (1/4/21-5/1/21) program implementation. The secondary endpoint was days of inpatient beta-lactam therapy. Implementation logistics, de-labeling rate, and antimicrobial therapy changes were evaluated. Results: The program evaluated 392 individuals, with 184 and 208 patients comprising the pre- and post-intervention groups, respectively. The post-intervention period was associated with an increase of 19.8% in complete allergy histories (0.359 PPc; R 2 0.26; p = 0.002) and 9.34 beta-lactam DOT per 1,000-days-present (1.106 PPc; R 2 0.194; p = 0.009). Conclusion: Implementation of a comprehensive beta-lactam allergy management program was associated with higher rates of complete beta-lactam allergy history and beta-lactam use.